Hubungan Pola Makan Dengan Status Gizi Anak Usia 3-5 Tahun Di Wilayah Kerja Puskesmas Bontokassi Galesong Selatan: The Relationship of Dietary Patterns With The Nutritional Status of Children Aged 3-5 Years in The Working Area of Bontokassi Health Center South Galesong - Sah Puteri, Sri Kurnia; Kartini H, Anita; Nuryana, Riska; Sumarmi, Sumarmi (Jurnal Keperawatan Muhammadiyah, 2024)
This research aims to determine the relationship between eating patterns and the nutritional status of children aged 3-5 years in the working area of the Bontokassi Public Health Center in 2023. This research uses an Analytical Survey research design, using a Cross Sectional approach. The sample in this study was all children aged 3-5 years who had poor and good nutrition, namely 31 respondents. Data collection techniques used in this research is the Total Triangle Sampling Technique (a combination of observations through observations carried out directly on the implementation of the research, then interviews and documentation are carried out. This research was analyzed using SPSS with the chi-square test. Results are presented in the form of tables and narratives. The results of this research were obtained The value of ρ = 0.000 so that ρ < α then the Ha research hypothesis is accepted, meaning there is a relationship between diet and the nutritional status of children 3-5 years old in UPT Puskesmas Bontokassi in 2023. Conclusion: The diet of children aged 3-5 years in the UPT Working Area of ​​the Bontokassi Community Health Center is mostly classified as having a good diet (63.9%) and the nutritional status of children aged 3-5 years in the UPT Working Area of ​​the Bontokassi Community Health Center is mostly included in body weight. which is in accordance with WHO standards (63.9%).